Penggunaan Media Gambar sebagai Upaya Meningkatkan Hasil Belajar Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) Siswa Kelas VII.H SMP Negeri 1 Mataram - Fitriah, Hayatun (TSAQOFAH, 2023)
This study aims to improve learning outcomes through the use of media images. This research is a class action research, the research subjects are students of class VII.H SMP Negeri 1 Mataram. This research was conducted in three cycles, each cycle carried out based on four stages, namely: planning, implementing, observing, and reflecting. Of all the activities of implementing action research in class VII.H of SMP Negeri 1 Mataram on the subject matter of Humans, Places, and the Environment carried out in three cycles it can be concluded that the learning outcomes of class VII.H students of SMP Negeri 1 Mataram for the 2022/2023 academic year, using media images can be improved with the final result of the study is the class average before the action 77.87 or 68.42% classical completeness, to 78.79 or 76.32% classical completeness in cycle I, increased to an average of 80 .50 or 84.21% in cycle II and experienced an increase to an average test of 84.18 or 97.37% in cycle III. From the results of student observations it was shown that there was an increase in student activity in cycle I obtained a score of 17 or 60.70% to 20 or 71.43% in cycle II and 23 or 85.71 in cycle III. The increase in student activity in social studies learning is supported by the increase in teacher activity in maintaining and improving the learning atmosphere using media images, this can be seen from the observations of teacher activities where in cycle I a score of 22 or 61.10% was obtained, becoming 26 or 72.23 % in cycle II and increased to 33 or 86.12% in cycle III.